Pengajaran (BIPA) Bahasa Indonesia bagi Penutur Asing Berbasis Budaya - Andini Kurnia Fitriana; Mochamad Whilky Rizkyanfi; Arie Sugiyartati (Jurnal Sosial Humaniora dan Pendidikan, 2026)
BIPA (Indonesian for Speakers of Other Languages) is one of Indonesia's strategic approaches to introducing the nation's identity, character, and cultural heritage to the global community. It serves as the primary gateway for foreign learners to become familiar with Indonesia, its language, and its diverse cultural values. Consequently, BIPA instruction is inseparable from the teaching of Indonesian culture. Cultural elements are integrated into language learning through the four fundamental language skills that characterize BIPA instruction: reading, writing, speaking, and listening. Through this integrated approach, learners not only develop Indonesian language proficiency but also gain a deeper understanding of the cultural context in which the language is used.